أثر نظم دعم القرار(DSS) في إدارة الأزمات بالتطبيق على شركة الاتصالات اليمنية (MTN) - مانع, عبدالرحمن أحمد (Journal of Amran University, 2022)
This study aimed at measuring, and analyzing the role of decision support systems (DSS) in crisis and disaster management in the Yemen Telecom Company (MTN), where the study population consisted of (70) employees and managers of the telecom company. The questionnaire was improved to measure the variables of the study, which consisted of 3 axes and 38 paragraphs, and a number of appropriate statistical methods were used. The study reached a number of results; The Question Was answered that there Is a Strong Correlation between Decision Support Systems Represented in its Dimensions (Technological, Human, and Top Administration support) and Crisis and Disaster Management from the Point of view of the research Sample and That there are factors that help to deal with Crises and Disasters Efficiently and Effectively to a large extent from the Point of view of the research sample. View of the research sample, and the presence of obstacles to a moderate degree from the Point of view of the research sample.